Implementation of a Pilot Leadership Curriculum for Physical Medicine and Rehabilitation Residents. (February 2021) - McIntyre, McKyla; Alavinia, Seyed Mohammad; Matlow, Anne
Abstract : Abstract: Medical trainees are expected to achieve leadership competencies by the end of their training. However, there is a lack of standardized postgraduate leadership education. The aims of this study were to evaluate a pilot program consistent with leadership aims of the medical education body and to assess learners' perceived responses to the curriculum. A pilot workshop was developed using Kern's six-step approach to curriculum development for medical education. Topics included leading teams, managing conflict, feedback, goal setting, and time management, as these gaps were identified during a targeted needs assessment. Learning was assessed by preworkshop and postworkshop self-assessments, and the curriculum was evaluated with a postworkshop survey. The workshop was attended by 14 physical medicine and rehabilitation residents and 1 medical student. There was a statistically significant increase in participants' Likert scale confidence scores for the summative areas of leading teams, managing conflict, feedback, goal setting, and time management ( P < 0.001). All participants rated the session as 4 or 5/5 on all evaluation domains. In conclusion, a single session targeting stated needs of trainees was successful in increasing perceived competence in areas relevant to clinical leadership. Expansion to include a longitudinal component, with assessment for behavior change for ongoing improvement would be beneficial. Abstract : Supplemental digital content is available in the text.